Design of Ribosome Binding Sites in Streptomyces coelicolor - Luo, Hong-Dou; Tao, Yang; Wang, Wen-Guang; Lin, Tao; Wang, Yue-Yue; Jiang, Hui (Current Proteomics, 2017)
Background: The ribosome binding site (RBS) containing Shine-Dalgarno (SD) sequence in prokaryotes plays an important role in identification of the translation initiation site within mRNA by ribosome. Objective: Our study aimed to improve the target protein production under translational level in prokaryotes by engineering of RBSs. Method: Two RBSs were designed in Streptomyces coelicolor M145, Sco-RBS* with an SD sequence which is completely complementary to 3'-end of 16S RNA and Sco-RBS0 with an SD sequence which is completely non-complementary to 3'-end of 16S RNA. The enhanced green fluorescent protein (EGFP) was used as a reporter, whose gene was transcribed and translated under the control of Sco- RBS*, Sco-RBS0, and a native RBS Sco-RBSactI in recombinant S. coelicolor strains. Results: Replacement of Sco-RBSactI with Sco-RBS* resulted in increase of both EGFP production and the ratio of EGFP to EGFP mRNA by 2.67-fold and 6.07-fold, respectively. Replacement of Sco- RBSactI with Sco-RBS0 resulted in decrease of both EGFP and the ratio of EGFP to EGFP mRNA by 4.35-fold and 2.18-fold, respectively. Conclusion: We provided a method to increase protein production at the translational level in Streptomyces.
Keywords: recombinant strains